Pharmaceutical quantification with univariate analysis using transmission Raman spectroscopy. (2nd September 2019) - Shimamura, Rie; Koide, Tatsuo; Hisada, Hiroshi; Inoue, Motoki; Fukami, Toshiro; Katori, Noriko; Goda, Yukihiro
Abstract: The purpose of this study was to investigate the quantification performance of transmission Raman spectroscopy with univariate analysis. Model dosage forms containing acetaminophen and an excipient, lactose monohydrate, were prepared. The Raman spectra of the tablets were obtained using the modes of transmission, backscattering micro-spectroscopy, and wide area illumination. Calibration curves for quantification of acetaminophen in the tablets were created using peak heights of the Raman spectra. Of the three modes of measurement, the quantitative results by transmission had the highest correlation with those by conventional UV–vis methods. In the validation of quantification by the transmission mode with univariate analysis, a certain degree of daily variation was confirmed. Additionally, quantitative results using peak heights were compared with those of partial least squares (PLSs) multivariate analysis. The root mean square error of prediction (RMSEP) suggested that quantification using PLS provided better precision than the peak height method as expected. However, content uniformity test using large sample sizes by the Raman spectra is not required to be very highly predictive because they usually employ non-parametric criteria and include wide specification ranges. Therefore, univariate analysis using transmission Raman spectroscopy was a suitable quantitative method for conducting content uniformity tests of large sample sizes.